Dynamic Structure-Soil-Structure Interaction in unsymmetrical plan buildings due to seismic excitation - Vicencio, Felipe; Alexander, Nicholas A. (Soil dynamics and earthquake engineering (1984), 2019)
This paper explores the influence of Structure-Soil-Structure Interaction (SSSI) between a pair of buildings, one of which is unsymmetrical in plan and hence subject to seismically induced coupled torsion/sway motions. A reduced-order parametric model of this system is proposed and validated using finite element analysis. A database of 15 strong ground motion records are employed. Over 3 million system/ground motion cases are analysed in this extensive parametric study. Results suggest that the SSSI can significantly affect the displacement and acceleration response of the unsymmetrical plan structures. Building torsion has the effect of increasing the building responses for a broader parametric range over which SSSI effects are significant. Additionally, a taller torsionally irregular building adjacent to a smaller building can in some parametric cases be adversely affected by SSSI. This finding contradicts results from previous studies, that were based on non-torsional, plan-regular, buildings, where the taller buildings are generally beneficially affected by the presence of smaller adjacent buildings. •The influence of SSSI can lead to significant changes in the response of the building, regardless of the earthquake event.•The SSSI effect has an important influence on the torsional mode in building 1 for a broad range of parameters.•A taller torsionally irregular building adjacent to a smaller building can be adversely affected by SSSI.